Polycythemia Vera Presenting as Cardiac Arrest: Novel Management Strategies. (22nd January 2019) - Davis, Mark I.; Courtney, Brian K.; Cohen, Gideon; Poon, Stephanie; Madan, Mina
Abstract : Acute coronary syndromes (ACS) usually occur in patients with multiple cardiac risk factors. In young adults, drug use and hypercoagulable states are common causes for ACS presentations. We report a case of a man in his early 30s who was diagnosed with polycythemia vera (PV) and had a cardiac arrest due to an anterolateral ST elevation myocardial infarction. We discuss his unique management and review the evidence on the management of arterial thromboembolism in PV patients.